A SCIENTIFIC ARTICLES PERFORMANCE EVALUATION OF TRAINING PROGRAM WITH MODEL OF BALANCE SCORECARD EVALUATION IN GARUDA INDONESIA TRAINING CENTER - Tambun, Frans Mangasa (Journal of Education Research in Administration and Management (JERAM), 2017)
PERFORMANCE EVALUATION OF TRAINING  PROGRAM WITH BALANCE SCORECARD EVALUATION MODEL IN GARUDA INDONESIA TRAINING CENTER